Numerical Analysis of Slope Stability Due to Excavation of Diversion Tunnel at Pamukkulu Dam Site, Indonesia - Wakhid Khoiron Nugroho; I Gde Budi Indrawan, Dr.; Nugroho Imam Setiawan (Geological Engineering Department Universitas Gadjah Mada, 2021)
Located in the Takalar Regency of South Sulawesi Province, the Pamukkulu Dam is planned to use a tunnel type as its diversion structure. One of the critical parts in the tunnel construction is the stability of portal slopes. This research aimed to estimate the effect of tunnel excavation on the stability of the portal inlet and outlet slopes under static and earthquake loads by using the finite element method. The slope stability analyses were carried out under conditions of prior to and after tunnel excavation. The input parameters used were laboratory test results in the forms of index properties and mechanical properties taken from rock core drilling samples, completed with the rock mass quality parameters based on the Geological Strength Index (GSI) classification. The Mohr-Coulomb failure criterion was used to model strength of the soil, while the Generalized Hoek-Brown failure criterion was used to model strength of the rocks. The results of rock cores analysis using the GSI method showed that the inlet tunnel slope consisted of four types of materials, namely residual soil, fair quality of basalt lava, good quality of basalt lava, and very good quality of basalt lava. Meanwhile, the outlet portal slope consisted of three types of materials, namely residual soil, good quality basalt lava, and very good quality basalt lava. The calculated horizontal seismic coefficient for the pseudo-static slope stability analysis was 0.0375. The analysis results of slope stability in the Y1 inlet section had a critical Strength Reduction Factor (SRF) value of 2.35 in a condition prior to the tunnel excavation and a critical SRF value of 2.34 after the tunnel excavation. The Y2 outlet section had a critical SRF value of 13.27 in a condition before tunnel excavation and a critical SRF value of 5.55 after the tunnel excavation. The earthquake load addition at the Y1 inlet section showed a critical SRF value of 2.05, both before and after the tunnel excavation. The Y2 outlet section showed a critical SRF value of 11.49 before the tunnel excavation and a critical SRF value of 5.54 after the tunnel excavation. The numerical analysis results showed that earthquake load reduced critical SRF values of the slopes. At the Y1 inlet section, the tunnel excavation did not have a significant effect on slope stability. It was demonstrated by an extremely small decrease in a critical SRF value of 0.43% for a condition without an earthquake load and an unchanged critical SRF in a condition with an earthquake load. At the Y2 outlet section, the tunnel excavation had a more significant effect on the slope stability. It was exhibited by the decrease in the critical SRF value of 58.18% in a condition without an earthquake load and a decrease in the critical SRF value of 51.78% in a condition with an addition of an earthquake load. However, the analysis of slope stability for both sections showed that all design slopes were above the required allowable safety factor value.